Natural occurrence of fusarium head blight, mycotoxins and mycotoxin‐producing isolates of Fusarium in commercial fields of wheat in Hubei. (29th May 2012) - Zhang, J.‐B.; Wang, J.‐H.; Gong, A.‐D.; Chen, F.‐F.; Song, B.; Li, X.; Li, H.‐P.; Peng, C.‐H.; Liao, Y.‐C.
<x xml:space="preserve">Abstract</x> Combined analyses of the natural occurrence of fusarium head blight (FHB), mycotoxins and mycotoxin‐producing isolates of Fusarium spp. in fields of wheat revealed FHB epidemics in 12 of 14 regions in Hubei in 2009. Mycotoxin contamination ranged from 0·59 to 15·28 μg g−1 in grains. Of the causal agents associated with symptoms of FHB, 84% were Fusarium asiaticum and 9·5% were Fusarium graminearum, while the remaining 6·5% were other Fusarium species. Genetic chemotyping demonstrated that F. asiaticum comprised deoxynivalenol (DON), 3‐acetyldeoxynivalenol (3‐AcDON), 15‐acetyldeoxynivalenol (15‐AcDON) and nivalenol (NIV) producers, whereas F. graminearum only included DON and 15‐AcDON producers. Compared with the chemotype patterns in 1999, there appeared to be a modest shift towards 3‐AcDON chemotypes in field populations during the following decade. However, isolates genetically chemotyped as 3‐AcDON were present in all regions, whereas the chemical 3‐AcDON was only detected in three of the 14 regions where 3‐AcDON accounted for 15–20% of the DON and acetylated forms. NIV mycotoxins were detected in seven regions, six of which also yielded NIV chemotypes. The number of genetic 3‐AcDON producers was positively correlated with amounts of total mycotoxins (DON, NIV and acetylated forms) or DON in wheat grains. Chemical analyses of wheat grains and rice cultures inoculated with different isolates from the fields confirmed their genetic chemotypes and revealed a preferential biosynthesis of 3‐AcDON and 4‐AcNIV in rice. These findings suggest the importance of chemotyping coupled with species identification for improved prediction of mycotoxin contamination in wheat.